DAMPAK PERJANJIAN INDONESIA-CHILE COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IC-CEPA) TERHADAP NILAI EKSPOR KERTAS INDONESIA - Alifian Idris; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzes the impact of the Indonesia-Chile Comprehensive Economic Partnership Agreement (IC-CEPA) on the value of Indonesian paper exports to Chile. The year 2017 was the beginning of Indonesia's cooperation with countries in Latin America, IC-CEPA was completed and signed by the Minister of Trade of the Republic of Indonesia Enggartiasto Lukita together with the Minister of Foreign Affairs of the Republic of Chile Heraldo Muñoz Valenzuela at the Ministry Office Overseas Chile. The objectives of the IC-CEPA agreement, among others, are: (a) Promote equitable economic growth and development through the creation of new opportunities for workers and businesses and improve the living standards of the people of the two countries, (b) Promote cooperation in several potential areas of the two countries; (c) Stimulating Indonesian business actors to target Chile's non-traditional markets; (d) Making Chile a bridge for Indonesia's export products in the Latin America region. This research uses qualitative methods, with data collection techniques through literature studies sourced from several books, journals, articles and internet sites. This research uses Liberalism perspective and International Cooperation theory. The results of this research indicate that within one year of the agreement, there was a not-too-significant increase in exports due to the pandemic which hindered the entry and exit of goods from Indonesia and Chile. In the paper trade, on the contrary, the constant decline in the value of Indonesia's paper exports to Chile is certainly very detrimental considering the many conveniences offered by IC-CEPA, especially in terms of trade. Keywords: IC-CEPA, Bilateral Trade, Paper Exports